2013
DOI: 10.3389/fnhum.2013.00089
|View full text |Cite
|
Sign up to set email alerts
|

Neural Processing of Facial Identity and Emotion in Infants at High-Risk for Autism Spectrum Disorders

Abstract: Deficits in face processing and social impairment are core characteristics of autism spectrum disorder. The present work examined 7-month-old infants at high-risk for developing autism and typically developing controls at low-risk, using a face perception task designed to differentiate between the effects of face identity and facial emotions on neural response using functional Near-Infrared Spectroscopy. In addition, we employed independent component analysis, as well as a novel method of condition-related com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 50 publications
3
49
1
Order By: Relevance
“…Although currently ASD can be reliably clinically diagnosed only beyond the second year of life, researchers are increasingly turning to studying infant siblings of individuals clinically diagnosed with ASD, as this population is at high risk for autism, showing more than a 15-fold increase in the likelihood of a positive clinical outcome (e.g., Ozonoff et al 2011). In addition to collecting behavioral measures that might correlate with later development of autism, a few studies have begun using fNIRS to investigate cortical differences between at-risk infants and low-risk or typically developing infants in the first year of life (Lloyd-Fox et al 2013, Fox et al 2013, Keehn et al 2013; see also Redcay & Courchesne 2008, for a study of neural engagement during speech processing in 2–3-year-olds with autism). Keehn et al (2013) raises the intriguing prospect that focal activation in key regions of the brain are less relevant to mediating the symptoms of ASD than imbalances in the maturation of functional connectivity among the network of regions subserving social cognition (see Section 4.7).…”
Section: Domain-specific Findings About Infant Cognitionmentioning
confidence: 99%
“…Although currently ASD can be reliably clinically diagnosed only beyond the second year of life, researchers are increasingly turning to studying infant siblings of individuals clinically diagnosed with ASD, as this population is at high risk for autism, showing more than a 15-fold increase in the likelihood of a positive clinical outcome (e.g., Ozonoff et al 2011). In addition to collecting behavioral measures that might correlate with later development of autism, a few studies have begun using fNIRS to investigate cortical differences between at-risk infants and low-risk or typically developing infants in the first year of life (Lloyd-Fox et al 2013, Fox et al 2013, Keehn et al 2013; see also Redcay & Courchesne 2008, for a study of neural engagement during speech processing in 2–3-year-olds with autism). Keehn et al (2013) raises the intriguing prospect that focal activation in key regions of the brain are less relevant to mediating the symptoms of ASD than imbalances in the maturation of functional connectivity among the network of regions subserving social cognition (see Section 4.7).…”
Section: Domain-specific Findings About Infant Cognitionmentioning
confidence: 99%
“…Adopting a similar approach, Fox et al (2013) presented 7-month-old high and low-risk infants with short movie clips of their mother or a stranger smiling or posing a neutral expression. This design permitted the investigators to disentangle differential responses to face type (familiar, novel), emotion (happy, neutral) and group (high vs. low risk).…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study by Fox and colleagues [23] on infants with a high- and low-risk for ASD (that is, children who did, and did not have an older sibling with ASD, respectively), found that high-risk infants did not show differentiated brain responses to happy expressions of familiar vs. unfamiliar people, as did the low-risk infants. Thus, more research is needed to determine whether individuals with ASD react to the emotions of familiar people in a normative way, and whether this is related to their everyday empathic functioning.…”
Section: Introductionmentioning
confidence: 99%